2013
DOI: 10.1166/jnn.2013.7784
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer Modified Magnetic Nanoparticles as Adsorbents for Removal of Dyes

Abstract: The recycling of dendrimers using an ultrafiltration membrane during wastewater treatment is extremely inconvenient. With the combination of magnetic nanoparticles (MNP) with dendrimers, the problem of the recovery of tiny particulate matter from an aqueous solution can be overcome using its magnetism. In this study, the coprecipitation method was adopted to prepare MNP, and then MNP-G(n) (n, generations of dendrimers) was prepared with the formation of the dendrimers on the surface of the MNP. The adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…PAMAM dendrimer-conjugated magnetic nanoparticles were used in an experiment to sorb Zn(Ⅱ) and an organic dye, RBk5, from water [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…PAMAM dendrimer-conjugated magnetic nanoparticles were used in an experiment to sorb Zn(Ⅱ) and an organic dye, RBk5, from water [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…XRD patterns were shown in Figure 2H. Six evident characteristic peaks at about 2θ 30.1, 35.1, 44.0, 53.9, 57.6,and 62.8 were due to crystal indexes of ( 220), ( 311), ( 400), ( 422), (511), and (440) of Fe 3 O 4 , which confirmed the cubic spinel phase of naked MNPs (Zhou et al, 2013). Moreover, Gn-MNPs and MNPs had analogical feature diffraction peaks, which proved that the progress of dendrimer modification did not alter the crystal phase of MNPs and MNPs were steady with magnetic property.…”
Section: Characterization Of Mnps and Gn-mnpsmentioning
confidence: 75%
“…Responding to external magnetic stimuli, MNPs can be selectively accumulated at a target site in biological systems and release guest molecules in a dosage-controlled fashion [31, 32]. Several in vitro studies have shown that MNPs, displaying multiple binding ligands, effectively discriminate target biomaterials from a mixture solution [33]. Furthermore, upon exposure to the magnetic field, the arrangement of MNPs on a surface can be controlled in various ways, resulting in the use of the MNPs for the development of novel cell culture scaffold [34].…”
Section: The Peptide–np Conjugationmentioning
confidence: 99%